2020
DOI: 10.1039/d0ob00253d
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric trehalose analogues to probe disaccharide processing pathways in mycobacteria

Abstract: Chemoenzymatic synthesis of azido-functionalised asymmetric trehalose analogues that are resistant to enzymatic degradation to probe carbohydrate processing pathways in mycobacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 24 publications
2
38
0
Order By: Relevance
“…In these studies, we observed that the asymmetric epimeric analogs, galactotrehalose and mannotrehalose, showed an 3 and 12-fold reduction in binding affinity respectively. These findings are compatible with our recent studies in Mycobacterium smegmatis which, unexpectedly, showed that 6-azidogalactotrehalose is incorporated into the mycobacterial cell envelope with a similar efficiency as 6-azido-trehalose via the M. smegmatis LpqY-SugABC transporter (12,13). This result indicates that Mtr LpqY is able to tolerate epimerization of the hydroxy group at the 4-position, whereas epimerization at the 2-position is less favored.…”
Section: Substrate Specificity Of Mtr Lpqysupporting
confidence: 92%
See 3 more Smart Citations
“…In these studies, we observed that the asymmetric epimeric analogs, galactotrehalose and mannotrehalose, showed an 3 and 12-fold reduction in binding affinity respectively. These findings are compatible with our recent studies in Mycobacterium smegmatis which, unexpectedly, showed that 6-azidogalactotrehalose is incorporated into the mycobacterial cell envelope with a similar efficiency as 6-azido-trehalose via the M. smegmatis LpqY-SugABC transporter (12,13). This result indicates that Mtr LpqY is able to tolerate epimerization of the hydroxy group at the 4-position, whereas epimerization at the 2-position is less favored.…”
Section: Substrate Specificity Of Mtr Lpqysupporting
confidence: 92%
“…As expected, given the lack of genes encoding for phosphotransferase systems in Mtb, Mtr LpqY did not recognize trehalose-6-phosphate. Modified trehalose derivatives have been developed as tools to probe trehalose processing pathways in mycobacteria; however, up until now, the structural basis for the selective recognition of these analogs was unknown (11)(12)(13). Notably, our STD NMR studies in combination with MST analyses support the uptake of the 6-azido-trehalose analog by the mycobacterial LpqY-SugABC transporter and explain the reduced affinity for this chemically modified substrate.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Recently our understanding of the role of the Mtb carbohydrate importers has improved and substrates for some of these systems have been identified ( Fenn et al, 2019 , Fullam et al, 2016 , Kalscheuer et al, 2010b , Parker et al, 2020 , Furze et al, 2021 , Lowery et al, 2015 ). Interestingly, it has been shown that the Mtb LpqY-SugABC transporter specifically recycles trehalose from the mycobacterial cell envelope and is essential for Mtb virulence ( Kalscheuer et al, 2010b , Furze et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%